Atypical Exanthem as Cutaneous Manifestation Related to COVID-19 at a Primary Healthcare Facility - Prasetyadi Mawardi; Danu Yuliarta; Waode Nuraida (Acta Medica Indonesiana)
Coronavirus disease (COVID-19) infection attacks the mucosal structures of the respiratory tract, especially the bronchial mucosa and immune cells. The skin changes and manifestations related to COVID-19 infection remain not clearly understood. Cutaneous manifestations related to COVID-19 had been reported. Our patient manifested atypical cutaneous exanthem on her legs, with no other abnormalities found. We used oral azithromycin 500 mg, dexamethasone 0.5 mg, vitamin C 100 mg, and paracetamol 500 mg, which are available at Badak Baru Primary Health Care. The exanthem has improved after 10 days of treatment.